Molluscum contagiosum superimposed on congenital melanocytic nevus. - Pisani, V.; Garofalo, L. (European Journal of Pediatric Dermatology, 2011)
Case report. A child enrolled in a program of periodic monitoring of congenital melanocytic nevi was observed at the age of 6 years for the presence on his nevus of an about 3 mm in diameter papule with inflammatory appearance (Fig. 1). The dermoscopic examination showed punctate and irregular telangiectasias in absence of pigment, thus resembling Spitz nevus. A whitish dot-like papule was seen at a distance of 1 cm (Fig. 1, arrow). After 5 months the child returned to the control visit. His parents told us that the inflammatory papule had regressed spontaneously. The smaller whitish papule had become larger and measured 2 mm (Fig. 3); the dermoscopy examination showed a small central depression (Fig. 4). The papule was removed by curettage under local contact anesthesia and the histological examination confirmed the clinical diagnosis of molluscum contagiosum.